Walnut‐Derived Peptide PW5 Ameliorates Cognitive Impairments and Alters Gut Microbiota in APP/PS1 Transgenic Mice. Issue 18 (4th July 2019) - Wang, Min; Amakye, William Kwame; Guo, Lu; Gong, Congcong; Zhao, Yuanhui; Yao, Maojin; Ren, Jiaoyan
Abstract : Scope: Decreasing β‐amyloid (Aβ) accumulation is of significance in finding therapeutic candidates for cognitive impairments in Alzheimer's disease (AD). The aim of this study is to investigate the potency of the active components of walnut protein in decreasing Aβ aggregation and ameliorating cognitive impairments. Methods and results: Cell model of intracellular Aβ42 aggregation is used to explore the active ingredients in walnut protein hydrolysate (WPH). A bioactive peptide (Pro‐Pro‐Lys‐Asn‐Trp, PW5) with great anti‐Aβ42 aggregation activity identified from the WPH is synthesized for in vitro and in vivo experiments. Using classic APP/PS1 mouse model, it is validated that PW5 exerts its effects on cognitive improvement through reducing Aβ plaques accumulation. Moreover, metabolomic analysis reveals that serum norepinephrine (NE) and isovalerate levels are significantly increased in response to PW5 intervention, with decreased serum levels of acetylcholine (AChe) and valerate, compared with the vehicle‐treated APP/PS1 mice. PW5 feeding also improves gut dysbiosis in APP/PS1 transgenic mice by increasing the relative abundance of Firmicutes and decreasing Proteobacteria and Verrucomicrobia as displayed by 16s rRNA analyses. Conclusions: These promising results support the utilization of peptide PW5 as an active ingredient in functional foods or potential drug candidate for the prevention and/or treatment of AD. Abstract : Walnut ( Juglans regia L .) is a widely consumed nut as part of a regular diet. By using an intracellular β‐amyloid aggregation cell model and APP/PS1 transgenic mice, it is shown for the first time that a walnut‐derived peptide PW5 can effectively reduce β‐amyloid plaques and alter gut microbiota and serum metabolites compositions, and these are highly associated with cognitive improvements.